Aktualisasi Wakalah dalam Pembiayaan Murabahah di PT. Bank Aceh Syariah: Studi Komparasi Penerapan PSAK Nomor 102 - Muslina; Muhammad Adnan; Ridwan Nurdin (Institut Agama Islam Negeri (IAIN) Madura, 2025)
Actualization of Murabahah Financing at PT. Bank Aceh Syariah mostly implements murabahah transactions without orders. This model is classified by the bank into three models, namely murabahah application with additional wakalah contract, murabahah transaction plus wakalah and urbun and murabahah plus down payment without wakalah contract. In its operations, banking entities predominantly apply the first model for reasons of efficiency. This transaction requires recognition of the wakalah contract in the acquisition of the murabahah object. However, the bank did not present the agreement in its records so that the application of this model is not in accordance with the provisions of PSAK 102. This is the main focus for elaborating the provisions of PSAK related to the Murabahah Financing model and comparing the implementation at the Institution. The solution method used is descriptive qualitative with a case study approach to describe the phenomenon comprehensively. Based on the results of the analysis of observation data, interviews and documentation, it was concluded that PT. Bank Aceh Syariah has not followed PSAK in its entirety, especially the recognition of wakalah contracts, plus the lack of supervision in the procurement process of goods by customers, so that there are several cases of customers not buying what is listed in the murabahah contract.